A novel 3D video oculography system for measuring cross-axis vestibulo-ocular reflex. (October 2021) - Liang, Junfeng; Luong, Venus; McCraw, Josh; Schroeder, Alissa; Zhang, Ke; Gan, Rong; Dai, Chenkai
Highlights: Integration of an ALIO hexapod (ALIO Industries, Colorado, USA) to a video oculography (VOG) system. The system enables measuring vestibulo-ocular reflex of small animal under 6-degree of freedom motion real time. The motion accuracy of the present system is 10 folds higher than the previous single axis VOG built on a servo motor. Different approaches for eyeball tracking are compared for the implementation. Abstract: We present a video oculography (VOG) system with 6-degree-of-freedom (6-DOF) mobility for real-time measurements of the binocular 3D eye position of a small animal. A hybrid hexapod that allowed for multi-axis complex motions with the resolution of the microscopic level was used to control the motion of the animal. The instantaneous eyeball movement of the animal was determined based on two approaches: (1) tracking of marker arrays affixed to the cornea; and (2) tracking the pupil outline. The tracking of the eyeball movement and the motion control of the hexapod were implemented with the LabVIEW virtual instruments. Compared with our previous measurements using a servo-motor-based single-axis VOG system, positional error reduced from more than 4% to less than 0.7%. Validation showed that the tracking errors in three rotational axes are less than 2% for the magnitude and less than 5° for the direction angle. The present VOG system is an effective tool for cross-axis 3D vestibulo-ocular reflex study on small animals.